Impact of Behavior Biases on Perceived Trading Return - YASIR KHAN; DR. SAIMA BATOOL; ABDUL WAHEED KHAN (Journal of Business & Tourism, 2021)
The purpose of this study was to understand impact of behavior biases on perceived trading return in Pakistan Stock Exchange regarding investor from Khyber Pakhtunkhwa.The current research considered the whole investors of Khyber Pakhtunkhwa doing investment in First National Equities Limited and TAURUS Securities as population while 150 investors took as sample from each First National Equities Limited and TAURUS respectively, 300 questionnaires has been issued to the investors holding in mind that 100 of the respondents will return the questionnaires with good response. Simple random sampling technique used at the time of sending questionnaires to the investors from First National Equities Limited and Taurus in Pakistan Stock Exchange. Most managers and scholars emphasize that perceived trading return’s most important tool for gaining advantage is behavior biases and; in order to attain a success level at stock exchange for both investor and organization that must be awareness of behavior i.e. market as well as investor. Primary data of this research was collected particularly through using likert scale questionnaire from Investors from Khyber Pakhtunkhwa doing investment in Pakistan stock exchange. The data collected were then analyzed by way of factor analysis and multiple regression methods to validate the hypotheses formed in the theoretical framework